EXTRACTION OPTIMIZATION OF TRADESCANTIA SPATHACEA SW. LEAF CRUDE EXTRACT AND ANTHOCYANIN CONTENT - ANILÚ MIRANDA-MEDINA; PAOLA LIBERTAD GARCÍA-MEDEL; KAREN RODRÍGUEZ-MARTÍNEZ; PATRICIA MARGARET HAYWARD-JONES; DULCE MARÍA BARRADAS-DERMITZ; GEORGINA LUNA-CARRILLO (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Considering both the health and energy areas where anthocyanins have been revealing their real and potential applications, research on their extraction optimization methods is a priority. Conditions to achieve the highest mass of crude extract from Tradescantia spathacea leaves with the highest absorbance (A) in the region of 500 - 540 nm linked with anthocyanins, were investigated through a Box-Behnken design and response surface methodology. Independent variables involved in the Box-Behnken design were solvent (ethanol) concentration (30, 50, 70 % v/v), solvent/fresh leaf ratio (1.67:1, 2.34:1; 3:1 v/w) and extraction temperature (30, 50, 70 °C). Dependent (response) variables were crude extract amount and the extract with the maximum A in the region of 500-540 nm. Experimental values of A 500 - 540 nm were 0.3562 and 0.7558; crude extract mass ranged between 0.285 g and 0.7157 g, corresponding to a yield between 144 to 347 mg dried extract per g of dried leaf. Using a solvent/fresh leaf ratio of 3:1 v/w, 70 °C, 65 % ethanol, the highest values of both crude extract mass and A 500 - 540 nm were obtained.